2019
DOI: 10.1186/s13018-019-1102-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of different ankle MRI scanning planes for the anterior talofibular ligament injury diagnosis: a cadaveric study

Abstract: Background The objective of the current study is to compare reliability, accuracy, sensitivity, and specificity in magnetic resonance imaging (MRI) evaluation of anterior talofibular ligament (ATFL) among the routine axial scanning plane, oblique axial-coronal scanning plane, and oblique axial-sagittal scanning plane. Methods Twenty cadaveric feet were studied. ATFL was exposed before scanning. Routine axial, oblique axial-coronal, and oblique axial-sagittal MRI scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…Our result reported main causes of ankle pain was during stumping 45%, 17. 5% accidents, l0% during sport activity and 27.5% during football, it agreement with other study [18]. Nawroz et al recorded the cause of ankle sprains, the greatest patients were because accidents in 40%, 26% by sport, 18% by stumping and 16% by football [12].…”
Section: рис 3 мртsupporting
confidence: 86%
“…Our result reported main causes of ankle pain was during stumping 45%, 17. 5% accidents, l0% during sport activity and 27.5% during football, it agreement with other study [18]. Nawroz et al recorded the cause of ankle sprains, the greatest patients were because accidents in 40%, 26% by sport, 18% by stumping and 16% by football [12].…”
Section: рис 3 мртsupporting
confidence: 86%
“…MRI has the ability to display soft tissues and the advantages of noninvasiveness, rapid evaluation, multiplanar display, and no radiation damage. Numerous studies have reported that MRI examination has a high diagnostic value [ 7 9 ]. Kumar et al reported a sensitivity of ATFL tears of 60%, accuracy of 72%, and specificity of 87% [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial management of ankle injuries is the RICE protocol, which consists of rest, ice, compression, elevation, and analgesia [ 7 ]. Surgical treatment is rare and includes arthroscopy and reconstructive surgeries such as the modified Brostrom technique which is a well-recognized surgical technique used for the treatment of lateral ligamentous complex injuries for ankle instability and is now regarded as the reference standard technique [ 7 , 8 ]. The use of surgical treatment is typically limited to patients who fail conservative management [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment is rare and includes arthroscopy and reconstructive surgeries such as the modified Brostrom technique which is a well-recognized surgical technique used for the treatment of lateral ligamentous complex injuries for ankle instability and is now regarded as the reference standard technique [ 7 , 8 ]. The use of surgical treatment is typically limited to patients who fail conservative management [ 7 , 8 ]. The aim of this study was to explore the approach to patients with negative ankle MRI who continue to have symptoms of ankle instability despite conservative therapy in our institute.…”
Section: Introductionmentioning
confidence: 99%